The relationship between perceived stress and emotional intelligence in Moroccan nursing students - Jamal Ksiksou; Lhoussaine Maskour; Smail Alaoui (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Nursing students are subjected to many stressors during their clinical practicums. Emotional intelligence (EI) could act as a real stress regulator. In this perspective, we sought to study the relationship between stress and EI in a sample of Moroccan nursing students. MATERIALS AND METHODS: This study was conducted using the descriptive correlational method. The statistical population consisted of the nursing students of the Higher Institute of Nursing Professions and Health Techniques of Tetouan in Morocco during the academic year 2021-2022. Among them, 146 participants were selected on the basis of simple random sampling. Participants completed a self-administered questionnaire addressing sociodemographic factors, perceived stress (the Perceived Stress in Clinical Practice Scale), and emotional intelligence (Wong and Law Emotional Intelligence Scale test). Descriptive statistics were used and Pearson's correlation coefficient was applied to assess the correlation between stress and EI, and to compare them according to socio-demographic characteristics. A linear regression analysis was calculated to analyze the effect of independent variables on perceived stress and EI. For the analysis, a level of 0.05 was chosen. RESULTS: The overall mean age of the students was 20.02 ± 1.12 years. Participants had moderate levels of perceived stress (M = 2.42 ± 0.77) and high levels of EI (M = 3.79 ± 1.09). A significant positive correlation between perceived stress and EI was found (r = 0.741, P < 0,05). The regression model shows that EI, education level, and clinical practice setting can explain changes in perceived stress levels and are effective and significant factors (P < 0,001). CONCLUSION: EI has been shown to be a protective factor against stress in nursing students. Those with well-developed EI have lower levels of stress. Therefore, it is suggested that a mindfulness-based training program be incorporated into the nursing curriculum to develop emotional skills and combat stress in students.